An Assessment of the Role of Community Based Organisations (CBOS) in the Development of Ile-Ife - Elutilo, Taye Adeboye (2015)
The study investigated the structures, functions, achievements and problems of CBOs (social, primordial and occupational ) in Ile-Ife. This was with the view to revealing the weaknesses and prospects they possess for socio-economic development of the community. Primary and secondary materials on CBOs such as constitutions of the CBOs, minutes of meetings, journals, archival materials in the private libraries of some of the CBOs were consulted and utilized. For the primary data, three sets of questionnaire were used for the study, the first set comprised ninety questionnaires administered on three key officials (Chairmen, Secretaries and Treasurers) of the thirty CBOs selected for the study. The second set of questionnaires were administered on each of the five Quarters' Heads in Ile-Ife and ten persons purposively selected (on equal sex basis) from each of the five quarters. The third set of questionnaires was administered on six management staff of Community Development Department (CDD) of Ife East and Ife Central Local Governments. A total of 30 CBOs were examined in the ratio 16:14 respectively for Ife Central and Ife East LGAs. Data were analysed using frequency counts, percentages and tables. The result revealed that 83% of CBOs identified for the study were primordial; occupational 10% and social 7%. Their activities were carried out at committee levels such as finance, work, disciplinary and social; it was further revealed that there was inadequate finance from the local governments for the CBOs' projects. The study showed that only 5% of the total money spent on CBOs' projects especially in 2005 was derived from grant-in –aids received from local government councils, while levies, dues and fines generated from CBOs' members constituted their revenue. The major achievements of the CBOs were in the provision of social services such as construction of culverts, health centres, primary schools, community halls and erection of electric poles. It was also found that few CBOs' projects were not properly implemented because of lack of honestly and coordination among the CBOs' members, politicization of the delivery of social services, poor government policies and incessant communal clashes. The study concluded that the CBOs played credible roles as agents of development given their relevance and acceptability as partners in governance and community building.